The Effect of Eight Weeks Aerobic Training on Serum Ferritin Level, Glycemic and Lipid Indices in Women with Type 2 Diabetes - Atefeh Helmi Siyasi; Nahid Bijeh; Elham Hakak Dokht; Gholam Rasul Mohammad Rahimi (پیاورد سلامت, 2021)
Background and Aim: Recent studies indicate that increased body iron stores have been associated with the development of glucose intolerance and type 2 Diabetes. Ferritin is the most important iron storage protein in the body, which is used to evaluate disorders associated with iron metabolism. The aim of this study was to examine the effect of eight weeks of aerobic training on serum ferritin level, glycemic and lipid indices in women with type 2 Diabetes. Material and Methods: Twenty Diabetic women aged 45-55 years were selected voluntarily and divided into experimental (n=10) and control (n=10) groups. The experimental group participated in the aerobic training program for eight weeks, three 60-minutes sessions per week with an intensity of 55-65% of heart rate reserve. The control group did not participate in any activity during the intervention period. Serum ferritin, glycemic and lipid indices were evaluated before and after eight weeks and then data were analyzed by SPSS software. Results: Ferritin (P=0.012), insulin (P=0.004), fasting glucose (P=0.041), insulin resistance index (P=0.012), total cholesterol (P=0.041), and triglyceride (P=0.005) significantly decreased, while the mean of HDL(P=0.012) significantly increased in the experimental group. Moreover, the results showed that changes in ferritin (P=0.002), insulin (P=0.014), insulin resistance index (P=0.001) and TG (P=0.010) were statistically significant between the experimental and control groups. Conclusion: Women with type 2 Diabetes can benefit from moderate-intensity aerobic exercise programs to improve their glycemic and lipid profile, as well as iron metabolism abnormalities.